2017
DOI: 10.1016/j.kint.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Results of the HEMO Study suggest that p-cresol sulfate and indoxyl sulfate are not associated with cardiovascular outcomes

Abstract: Cardiovascular disease, the leading cause of mortality in hemodialysis patients, is not fully explained by traditional risk factors. To help define non-traditional risk factors we determined the association of predialysis total p-cresol sulfate, indoxyl sulfate, phenylacetylglutamine and hippurate with cardiac death, sudden cardiac death, and first cardiovascular event in the 1,273 participants of the HEMO Study. The results were adjusted for potential demographic, clinical, and laboratory confounders. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
0
59
2
Order By: Relevance
“…However, not all studies agree with these findings. In a large cohort of 1273 patients on dialysis, indoxyl sulfate and p-cresol were not associated with cardiovascular events (18). Only in a subcohort of patients on dialysis with low serum albumin was p-cresyl significantly associated with cardiovascular events (18), suggesting that other factors may modify this relationship.…”
Section: And Atherosclerosis (18) P-cresylmentioning
confidence: 98%
“…However, not all studies agree with these findings. In a large cohort of 1273 patients on dialysis, indoxyl sulfate and p-cresol were not associated with cardiovascular events (18). Only in a subcohort of patients on dialysis with low serum albumin was p-cresyl significantly associated with cardiovascular events (18), suggesting that other factors may modify this relationship.…”
Section: And Atherosclerosis (18) P-cresylmentioning
confidence: 98%
“…In both dialysis and nondialysis patients, free p‐creosol sulfate concentrations are associated with CVD and mortality. In analysis of HEMO study participants, there was no correlation between p‐cresol sulfate and indoxyl sulfate and cardiovascular outcomes; however, among patients with low albumin levels, there was such an association . AST‐120 is an orally administered binder that can adsorb small molecule uremic toxins and is used internationally to slow the progression of renal disease and improve uremic symptoms .…”
Section: Cardiovascular Changes In Uremic Patientsmentioning
confidence: 99%
“…For example, PCS and IS have repeatedly been associated with overall mortality, cardiovascular disease and progression of CKD [3][4][5]. Notwithstanding Shafi et al [20] failed to confirm an association between total PCS and IS and cardiovascular outcomes in prevalent HD patients in a latest post hoc analysis on the HEMO trial, a commentary in the same issue suggested that analytical issues and case-mix may explain the discrepant findings [21]. Serum 3-IAA concentration has been reported to be an independent predictor of mortality and cardiovascular events in patients with CKD [6].…”
Section: Discussionmentioning
confidence: 99%